ANALYSIS OF METAL Pb AND Cu CONTENT IN SEAGRASS (Sargassum sp) IN BAYUR BAYS OF WEST SUMATERA PROVINCE - Fitri, Yuliza; Siregar, Yusni; Amin, Bintal (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2021)
Located in Teluk Bayur bay the port is of the five biggest and busiest ports in Indonesia. High sea transportation activities and anthropogenic activities may lead to heavy metal pollution. The purpose of this study was to determine the concentration of Pb and Cu metals, in seagrass (Sargassum sp.) and to analyze the feasibility of consuming Sargassum sp. The method used in this study is a survey method, by analyzing heavy metal at Laboratory Pekerjaan Umum of Riau Province. The water quality temperatures 30-31oC, and salinity of 30-31 ppt, appeared curred velocity 0.06-0.08 m/sec, water transparency 100% with a depth of ± 1 m and pH 7. Pb concentrations the highest is 2.9367 μg/g at stations close to the port and the lowest is 2.2506 μg/g at stations close to tourist areas, and the concentration of Cu metal shows the highest 3.3850 μg/g at stations close to community settlements, and the lowest is 2.7772 μg/g near the port area of ​​Teluk Bayur. Based on the PTWI value, Sargassum sp. those originating from the waters of Teluk Bayur, West Sumatra, are still safe for consumption. Based on the Anova Pb and Cu tests in Sargassum sp. do not different (p> 0.05).